Pemanfaatan Limbah Plastik PVC Sebagai Bahan Tambah Pada Campuran AC-WC - Mita Rante; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
To support road construction and improve the quality of the asphalt mix, road construction requires good concrete asphalt and routine maintenance, one of which is by adding additives to the asphalt. Pipe waste made of PVC plastic is the material used. This PVC plastic waste is utilized by adding PVC plastic to the asphalt mixture using a dry method. The purpose of this study was to test the characteristics of the AC-WC mixture using PVC plastic waste as an added ingredient. Test method with conventional Marshall and Marshall Immersion. The results of the Conventional Marshall test show that by using plastic waste levels of 0%, 1%, 2%, 3% and 4%, the characteristics of the AC-WC mixture such as Stability, Flow, VIM, VFB, and VMA meet the 2018 Directorate General of Highways specifications and results Marshal Immersion testing shows Marshall Residual Stability shows the value meets the requirements.